2017
DOI: 10.1101/gr.213751.116
|View full text |Cite
|
Sign up to set email alerts
|

Small chromosomal regions position themselves autonomously according to their chromatin class

Abstract: The spatial arrangement of chromatin is linked to the regulation of nuclear processes. One striking aspect of nuclear organization is the spatial segregation of heterochromatic and euchromatic domains. The mechanisms of this chromatin segregation are still poorly understood. In this work, we investigated the link between the primary genomic sequence and chromatin domains. We analyzed the spatial intranuclear arrangement of a human artificial chromosome (HAC) in a xenospecific mouse background in comparison to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 94 publications
(122 reference statements)
2
26
0
Order By: Relevance
“…This is in agreement with recent independent locus-specific experiments. First, previous studies had suggested that regions of several hundred kb were long enough to correctly position themselves in vivo according to their chromatin state in the corresponding compartment (van de Werken et al, 2017). Second, super-enhancers that typically range in size between 10 and 25 kb were found to associate both in cis and in trans, especially in the absence of cohesin (Rao et al, 2017), indicating that interactions between these 10-25 kb elements are stable enough to facilitate their clustering.…”
Section: Discussionmentioning
confidence: 97%
“…This is in agreement with recent independent locus-specific experiments. First, previous studies had suggested that regions of several hundred kb were long enough to correctly position themselves in vivo according to their chromatin state in the corresponding compartment (van de Werken et al, 2017). Second, super-enhancers that typically range in size between 10 and 25 kb were found to associate both in cis and in trans, especially in the absence of cohesin (Rao et al, 2017), indicating that interactions between these 10-25 kb elements are stable enough to facilitate their clustering.…”
Section: Discussionmentioning
confidence: 97%
“…Cohesins, together with DNA/chromatin elements (2). In this context, the expansion of several families of transposable elements (TE) has provided new regulatory network for coordinated control of gene expression (3) and enabled more sophisticated avenues for genome organization (4,5). Short Interspersed Elements (SINEs), in particular Alu elements (AEs), represent the largest fraction of TE which have also evolved proto-enhancers function in the human genome (6).…”
Section: Introductionmentioning
confidence: 99%
“…Since AEs have been shown to evolve towards proto-enhancer function and the epigenetic state of enhancers participates in forging genome topology and gene expression (5,6), TFIIIC might help in reorganizing the landscape of chromatin loops upon SS. To explore this possibility, we compared genomic contacts by in nucleo Hi-C (24) and transcript levels by mRNA-seq in T47D cells grown in the presence of absence of serum.…”
Section: Introductionmentioning
confidence: 99%
“…Our model is agnostic of whether such attraction between heterochromatin is caused by affinity between homotypic repetitive elements 30,31 , or mediated by other proteins (e.g. HP1) 32,33 .…”
mentioning
confidence: 99%